WHO five moments for medication safety among diabetic patients in Saudi Arabia - Ayat ElZayat; Rawaa Jilani; Assel Krimly; Lamar Awan; Lamar Alsiamy; Nawal Baeshin (PLoS ONE, 2026)
Background Diabetic patients are particularly vulnerable to medication errors. Assessing adherence to the WHO Five Moments for Medication Safety among diabetic patients is essential for identifying gaps in practice and improving patient safety in this high-risk group. This is the first study to assess medication practices based on the WHO Five Moments among diabetic patients in Saudi Arabia. Methods This cross-sectional study was conducted on 473 adult diabetic patients in Jeddah, Saudi Arabia. Patients completed a structured, self-administered questionnaire. The questionnaire comprised questions of the WHO Five Moments for Medication Safety. Content validity was confirmed through expert review, translation to Arabic followed forward–forward-backward procedure, and pre-testing confirmed face validity. Results Diabetic patients generally exhibited the highest practice in moment two: taking medications (72%) and the lowest in moment five: stopping medications (54%), and 66% showed high overall medication safety practice. Multiple regression identified that following a regimen, using hypoglycaemic medication or insulin, and controlled HbA1c as positive predictors of total medication safety scores (P-value <0.05). Conclusion Diabetic patients in Saudi Arabia generally exhibited overall a high adherence to the “Five Moments for Medication Safety,” with the highest practice in taking medications and the lowest in stopping them.